Comparison of Microscan Broth Microdilution, Synergy Quad Plate Agar Dilution, and Disk Diffusion Screening Methods for Detection of High-Level Aminoglycoside Resistance in Enterococcus Species - Murdoch, David R. (American Society for Microbiology, 2003)
We compared the dried MicroScan microdilution panel, Synergy Quad plate agar dilution, and high-potency disk diffusion screening methods for the detection of high-level aminoglycoside resistance in 815 enterococcal bloodstream isolates. Agreement between the three methods was 99% when testing for high-level gentamicin resistance and 96% when testing for high-level streptomycin resistance.